Economic Trends in Africa : The Economic Performance of Sub-Saharan African Countries - Dhonte, Pierre (IMF Working Papers; Working Paper ;, 1993)
This paper surveys recent economic developments in countries in the African Department. In the aggregate, output growth continues to be sluggish, and it is expected that half of the countries will experience a declining income per capita in 1993. However, structural adjustment is making fast progress, especially as regards the liberalization of exchange and credit markets. This bodes well for an eventual improvement in economic performance.